2005
DOI: 10.1007/s00018-004-4461-9
|View full text |Cite
|
Sign up to set email alerts
|

New antimicrobial activity for the catecholamine release-inhibitory peptide from chromogranin A

Abstract: Catestatin (bCGA(344-364)), an endogenous peptide of bovine chromogranin A, was initially characterized for its effect on the inhibition of catecholamine release from chromaffin cells. Catestatin and its active domain (bCGA(344-358)) were identified in chromaffin cells and in secretion medium. The present study identified a potent antimicrobial activity of bCGA(344-358) in the lowmicromolar range against bacteria, fungi and yeasts, without showing any haemolytic activity. Confocal laser microscopy demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
177
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(187 citation statements)
references
References 50 publications
5
177
0
1
Order By: Relevance
“…[ 52 ] They showed that bovine cateslytin (in the low micromolar range) readily crosses the cell membrane of fungi and rapidly reaches the intracellular space. Then the growth was arrested as soon as the peptide penetrated into the developing fungus.…”
Section: Bacterial Assaysmentioning
confidence: 99%
“…[ 52 ] They showed that bovine cateslytin (in the low micromolar range) readily crosses the cell membrane of fungi and rapidly reaches the intracellular space. Then the growth was arrested as soon as the peptide penetrated into the developing fungus.…”
Section: Bacterial Assaysmentioning
confidence: 99%
“…catestatin acts to stabilize baseline conditions in several in vivo and in vitro models (2,5,15,30,34,48). As such, the role of catestatin may not be apparent until an appropriate stimulus is applied.…”
Section: R723 Pacap Is Hypotensive In the Presence Of Catestatinmentioning
confidence: 99%
“…A series of studies on the antimicrobial function of the CGA-derived peptides has been conducted (19)(20)(21)(22). Catestatin (derived from the C-terminus of bovine CGA) is expressed in murine skin in response to injury and infection, and it has a potent antimicrobial activity against bacteria, fungi and yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Similar activity has also been reported for vasostatin-I (CGA1-76; corresponding to CGA residues 1-76), which can trigger the selective migration of human monocytes and eosinophils. CGA1-76 and catestatin have been described to be innate immunity components of mammals (19,21). A study by Lugardon et al (19) showed that the C-terminal moiety of bovine CGA1-76 exhibited a potent antifungal activity and that the disulfide-bridge loop Cys 17 -Cys 38 was crucial for its antibacterial activity, but not for the antifungal activity.…”
Section: Introductionmentioning
confidence: 99%